The agreement between wearable sensors and force plates for the analysis of stride time - Slattery, P.; Lizama, L. E. C.; Wheat, J.; Gastin, P.; Dascombe, B.; Middleton, K. (ISEA Engineering of Sport 14 Conference, 2022)
Stride time (ST) fluctuations contain long-term correlations and provide important information about locomotor health [1]. Linear and non-linear ST analysis methods have differentiated between healthy locomotor function and those at risk of falls [2], motor diseases [3] or with previous history of injury [4]. A recent systematic review reported that wearable sensors demonstrated excellent validity and reliability for calculating linear ST metrics, and poor-to-moderate validity and reliability for non-linear ST metrics [5]. A low number of high-quality studies, varying methods, and limited number of strides were cited as potential reasons for the findings. Therefore, this study aimed to assess the agreement between several wearable sensors and force plates in quantifying ST variability using published recommended methods [6].